Early Exploration in Mesopotamia - Pallis, P. K. (1954)
1693-1851; List of Assyro-Babylonian cuneiform texts published before 1851; wiederholt S. A. Pallis, The Antiquity of Iraq. A Handbook of Assyriology (Copenhagen 1956) Chapter II § 8 (= 70-87).